Is there a relationship between lower-extremity injuries and foot postures in professional football players? A prospective cohort study - Cherati, A. S.; Soltani, S. K.; Moghadam, N.; Hassanmirzaei, B.; Haratian, Z.; Soltani, S. K.; Rezaei, M. (Science and Medicine in Football, 2022)
Background: Lower extremity injuries are an ongoing concern for professional football players. This study aims to evaluate the relationship between foot posture and lower extremity injuries in professional football players. Method: In this prospective cohort study, 420 male players of the Iran Premium football league were evaluated during the 2015-2016 season. The players were assessed for their foot types based on optical and static foot scans and foot posture index (FPI). The trained club physicians recorded all injuries during the season. Result: The analyzed data of 244 players showed the highest rate of lower extremity injury in hamstrings, ankle, and groin, respectively. These injuries led to 46% of time loss. The probability of hamstrings injuries was higher among pronated players based on static, optic, FPI, and visual examination, 2.1, 1.8, 1.8, and 2.3, respectively. Medial Collateral Ligament (MCL) injuries were associated with subtalar joint abnormality defined by visual observation. An increased relative risk of leading-to-absence injuries among the flat foot group was significant based on optic scanning, FPI, and visual observation. Conclusion: Abnormal foot postures in professional football players may increase the risk of hamstring and MCL injuries and time loss due to lower extremity injuries.